Alchemical tafsīr: Qur’anic Hermeneutics in the Works of the Twelfth-Century Moroccan Alchemist Ibn Arfaʿ Raʾs - Todd, Richard (Islam and Christian-Muslim relations, 2023)
Beside the codenames and esoteric symbols inherited from Graeco-Egyptian antiquity, the later Arabic alchemical tradition also adopted motifs drawn from the Qur’an: from the blessed olive tree of the famous Light Verse (Q 24.35) to the burning bush and Moses’ staff. This interweaving of scripture and alchemical theory is especially noticeable in one of the major works of the post-Jābirian corpus, Shudhūr al-dhahab (Shards of Gold) by the Moroccan poet Ibn Arfaʿ Raʾs (fl. sixth/twelfth century), as well as in Ibn Arfaʿ Raʾs’s self-penned commentary, Ḥall mushkilāt al-Shudhūr (The Solution to the Obscurities in the ‘Shards’). But was the use of such motifs simply a literary device or did Ibn Arfaʿ Raʾs claim to discern a hidden alchemical meaning embedded in the qur’anic text? Focusing on this unexplored strand of the Islamic exegetical tradition, this article examines the premises put forward by Ibn Arfaʿ Raʾs in support of an alchemical reading of scripture.